Evaluate the reality of implementing the main electoral processes according to the quality management system In the Electoral Commission – Iraq - et.al, Assist. Prof. Dr. Maha Kamel Jawad , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The aim of the research is to recognize the role of quality management in the work of electoral bodies, with international interest in electoral work, as well as the need for electoral processes to be honest, fair and transparent. The commitment of commission to established regulations and laws and the observance of the rights of beneficiaries (workers, voters, candidates, political entities) are important matters that must be taken into account in order to enhance its credibility through improved quality of services provided. The problem of research in the face of electoral organizations and bodies in many countries, especially developing countries, is the limited application of quality and transparency standards in electoral processes, and the need to take advantage of the provisions of the International Standard ISO/TS 54001:2019, especially since commission needs to raise the quality of services provided by it to its beneficiaries. The research is important because it provides a framework for achieving the quality management requirements of electoral bodies in terms of key processes through the application of ISO/TS 54001:2019, and the importance of the proper design and implementation of the electoral quality management system on the one hand and the legal and political framework of the country on the other. The case study methodology, the use of check lists, and the benefits of the application of quality management in electoral bodies have been addressed, along with an assessment of the realities of the work of the Electoral Commission and an indication of its compatibility with the main electoral processes according to the specification. ISO/TS 54001:2019 Search results showed electoral process application rates at the electoral Commission ranging from (%100-50) compared to standard implementation of these processes. Among the most important recommendations of the research is the call for the adoption of the quality management system for electoral organizations and the adoption by the Electoral Commission of the implementation of the key processes of the International ISO/TS 54001:2019, the promotion of the quality culture and development of the Commission, as well as the promotion of the quality and development of the Commission. The potential, resources available and the use of competencies to enhance partner satisfaction, and to continuously improve the electoral process